Recent Advances in Machine Learning and Computational Intelligence - Wu, Yue; Zhang, Xinglong; Jia, Pengfei (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Machine learning and computational intelligence have been applied to various areas and witnessed many successes. The research in this publication explorse many intelligent algorithms which are characterized by computational adaptability, robustness, and high performance. These algorithms facilitate intelligent behavior in complex and dynamic environments and the development of technology that enables machines to think, behave, or act in a more humanesque fashion. This reprint aims to present and discuss the most recent innovations, trends, concerns, challenges, solutions, and application fields in the areas of machine learning and computational intelligence.